Raised at Rutgers : a President's Story. - McCormick, Richard L. (Rivergate Regionals Collection., 2014)
In Raised at Rutgers, Richard L. McCormick tells what it is like to run a major state university and vividly portrays the often contentious environment in which a university president operates today. He unsparingly recounts his decade of leadership, including his own missteps-those we know about and those we didn't-as he strove to obtain adequate resources for the university, to overhaul the often confusing organization of the New Brunswick campus, to manage the growth and success of intercollegiate athletics, and to deepen Rutgers's acceptance of its obligations as the state university.